Pengaruh Model Mobilitas Terhadap Konsumsi Energi Protokol Routing Optimized Link State Routing (OLSR) Pada Mobile Ad Hoc Network (MANET) - Hans Romario Sitorus; Primantara Hari Trisnawan; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Mobile ad hoc Network (MANET) is a dynamic communication network that can exchange information wirelessly by mobile nodes. This study is using Optimized Link State Routing (OLSR) as a protocol routing which is a proactive routing protocol. The main characteristic of a proactive routing protocol is a protocol that continually updates toward network topology changes by exchanging topology information at each node continuosly. This causes the proactive protocol requires high power. The mobility of mobile node on MANET also has several models including Random Waypoint, Random Walk, and Random Direction. With the nature of OLSR routing protocol that requires high power and the characteristic of mobile nodes on MANET networks that have limited power, it is necessary to know the influence of mobility models on energy consumption to build a MANET network with OLSR routing protocol efficiently. The testing scenarios in this study use two scenarios, which are based on the mobility models and based on the number of nodes. In the total energy consumption scenario with 20, 40, 60, 80, and 100 number of nodes and with Random Waypoint, Random Walk and Random Direction mobility models shows that the total energy consumption on Random Waypoint mobility has a significant difference compared to other mobility models. This is indicated by the percentage of total residual energy on Random Waypoint is 17.48% while Random Direction is 21.36% and Random Walk is 21.05%. In the average energy consumption scenario, each mobility model has increased the average value of energy consumption as the number of nodes increases with the number of nodes scenario of 20, 40, 60, 80, and 100 nodes. But in the Random Waypoint model, there is a decrease in average value of energy consumption from 791.941523 Joule at 40 number of nodes to 766.603226 Joule at 60 number of nodes. Whereas for the Random Walk and Random Direction mobility models, there was no decrease in the average value in any number of nodes scenario.